Restorative justice : prison as Hell or a chance for redemption? - Furio, Jennifer (New York : Algora Pub., 2002)
America keeps expanding its prisons - despite the lack of any credible evidence to show that this punitive view of justice provides safer communities and reduces crime. How is this justice system serving us? Restorative justice, as presented here, involves the recognition that criminals can be reformed and rehabilitated and that current models of punitive justice often cause even more pain while failing to help crime victims or reduce crime. The author explains what a system of restorative justice would look like, examining issues of parole, victim restitution, and human agency. Nearly two-thirds of the text is occupied by an excerpt from a memoir of a female offender, illustrating some of the issues discussed in other sections of the book.
What is restorative Justice? -- Principles of restorative justice -- Measuring results in restorative justice -- Can the process be too forgiving? : parole and determinate sentencing -- Faith, restorative justice and prison fellowship -- Bringing criminals to their victims -- What is just? : an examination of punishment and grace -- Linda's story, a memoir -- Linda's profile--and her integration back into society -- A global examination of restorative justice -- Family involvement in restorative justice -- Children and restorative justice -- A final analysis.
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: Restorative justice; Victims of crimes; Criminals -- Rehabilitation; Corrections -- Philosophy; Criminal justice, Administration of -- United States; Justice réparatrice.; Réhabilitation.; Services correctionnels -- Philosophie; Justice pénale -- Administration -- États-Unis.; SOCIAL SCIENCE -- Penology; Corrections -- Philosophy; Criminal justice, Administration of; Criminals -- Rehabilitation; Restorative justice; Victims of crimes; United States